The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fnsys.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuromodulation

Abstract: We describe a model of neurological disease based on dysfunctional brain oscillators. This is not a new model, but it is not one that is widely appreciated by clinicians. The value of this model lies in the predictions it makes and the utility it provides in translational applications, in particular for neuromodulation devices. Specifically, we provide a perspective on devices that provide input to sensory receptors and thus stimulate endogenous sensory networks. Current forms of clinically applied neuromodula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 137 publications
0
21
0
Order By: Relevance
“…TLNS is known to modulate sensorimotor and vestibular functions and is hypothesized to modulate multiple physiological processes via bottom-up neuromodulation of global brain function to augment neuroplasticity (Herrick and Keifer, 1998 ; Buisseret-Delmas et al, 1999 ; Marano et al, 2005 ; Wildenberg et al, 2010 , 2011 ). Current models emerging from other neuromodulation technologies, such as deep brain stimulation, have increasingly interpreted the effects as being comparable to neuromodulation through a sensory organ, with access to the same pathways and translated in similar ways as natural environmental stimuli (Black and Rogers, 2020 ). This concept is consistent with exercise-induced neuroplasticity effects cascading across the molecular, cellular, structural, functional, and behavioral levels (El-Sayes et al, 2019 ) along with demonstrated neuroprotective effects of trigeminal nerve stimulation in TBI (Chiluwal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…TLNS is known to modulate sensorimotor and vestibular functions and is hypothesized to modulate multiple physiological processes via bottom-up neuromodulation of global brain function to augment neuroplasticity (Herrick and Keifer, 1998 ; Buisseret-Delmas et al, 1999 ; Marano et al, 2005 ; Wildenberg et al, 2010 , 2011 ). Current models emerging from other neuromodulation technologies, such as deep brain stimulation, have increasingly interpreted the effects as being comparable to neuromodulation through a sensory organ, with access to the same pathways and translated in similar ways as natural environmental stimuli (Black and Rogers, 2020 ). This concept is consistent with exercise-induced neuroplasticity effects cascading across the molecular, cellular, structural, functional, and behavioral levels (El-Sayes et al, 2019 ) along with demonstrated neuroprotective effects of trigeminal nerve stimulation in TBI (Chiluwal et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…If so, this would suggest that central neuromodulation may be accomplished not only by cutaneous vibratory stimulation to cymba of the external ear (16), but also by similar sensory stimulation of suboccipital musculature, at least in babies. Other examples of sensory neuromodulation have been reported in the literature (37).…”
Section: Discussionmentioning
confidence: 94%
“…In concordance with their central role in many regulatory processes the vestibular nuclei have extensive projections to other brainstem nuclei (37). This means that any vestibular dysregulation present may well be propagated to those very same nuclei, particularly of the autonomic system (13), which may conceivably lead to a spectrum of associated symptoms such as listed in the introduction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Non-invasive methods of neural system stimulation operate at large spatial scales, and they can be by direct application of electrical or magnetic fields or by the use of sensory stimuli to modify neural activity [32, 44]. The non-invasive techniques are under active-research because of the potential clinical applications in humans.…”
Section: Discussionmentioning
confidence: 99%